Features of Acute Coronary Syndrome in Combination with Oncological Diseases in Elderly and Senile Patients - Z. D. Mikhailova; D. V. Pivovarov; A. R. Pivovarova (Архивъ внутренней медицины, 2021)
Relevance. The presence of oncological diseases, high polymorbidity in elderly and senile patients can lead to a complicated course of acute coronary syndrome, including the development of acute kidney injury and/or chronic kidney disease, which contributes to a deterioration of the immediate and long-term prognosis and an increase in mortality.The research purposes. To study the course of acute coronary syndrome depending on the presence or absence of oncological diseases in elderly and senile people and to identify clinical and laboratory-instrumental features.Materials and methods. The study included 200 patients (men — n=122 (61 %), women — n=78 (39 %), Me age — 69 (65;77) years). The patients were divided into two groups: 1) the main group — acute coronary syndrome in combination with oncological diseases (n=100) (men — n=61 (61 %), women — n=39 (39 %), Me age — 69 (65;77) years); 2) the comparison group — acute coronary syndrome without oncological diseases (n=100). The groups were formed by the copy-pair method in a ratio of 1:1 by gender and age. All patients were evaluated for anamnesis parameters, the total number of diseases, the Charlson comorbidity index, the main clinical and laboratory-instrumental parameters and the development of complications. We collected an average portion of morning urine on the first day of hospitalization to determine the content of KIM-1 (pg/ml) in 40 patients of the main group and 47 from the comparison group. We collected daily urine on the 2nd day of hospital treatment to determine the level of K+, Na+, Cl-, uric acid and albumin.The results. Patients of the main group, according to the anamnesis, were more often diagnosed with stable angina (p = 0.042), diabetic kidney disease (p = 0.017), chronic kidney disease (p = 0.013) and anemia (p = 0.008). In addition, these patients had a higher Charleson comorbidity index [8 (6; 9) and 5 (4; 6) points; p <0.001] and a total number of diseases [6 (5; 7) and 4 (3; 5); p <0.001]. Patients with oncological diseases with the development of acute coronary syndrome more often complained of shortness of breath (p=0.008) and heart rhythm disturbance (p=0.004). In patients of the main group a lower left ventricular ejection fraction was diagnosed [51.0 (44; 55) and 54 (48; 57), p=0.013]. Acute kidney injury was more frequently diagnosed in the study group than in the comparison group (p <0.001), including acute kidney injury by “basal” creatinine (p=0.005), acute kidney injury by creatinine dynamics (p=0.047), and acute kidney injury by chronic kidney disease (p=0.003). The KIM-1 leel in patients of the main group was higher [921.0 (425.1; 1314.8) and 658.0 (345.6; 921.4) pg/ml; p=0.011]. In patients with acute kidney injury, in contrast to patients without acute kidney injury, a higher level of KIM-1 was detected [999.2 (480.8;1314.1) and 663.1 (360.5;905.2) pg/ml; p=0.008]. Patients with acute coronary syndrome and oncological diseases in the hospital were more likely to develop urgent complications (p=0.005), including death (p=0.024) and acute heart failure (p <0.001). They also had a higher incidence of early post-infarction angina (p=0.018) and anemia (p=0.005).Conclusions. Our study found that patients in the main group had a higher Charlson comorbidity index, a greater number of diseases, including stable angina, diabetic kidney disease, chronic kidney disease, and anemia. These patients with the development of acute coronary syndrome more often complained of shortness of breath and heart rhythm disturbance. Patients with oncological diseases were more often diagnosed with acute kidney damage, including “basal” creatinine, creatinine dynamics, and chronic kidney disease. The level of KIM-1 in the urine was higher in this group of patients. Patients of the main group in the hospital were more likely to develop urgent complications, including acute heart failure and death. There was also a high incidence of early post-infarction angina and anemia.